Insights into the Genetic Relationships and Breeding Patterns of the African Tea Germplasm Based on nSSR Markers and cpDNA Sequences - Wambulwa, Moses C.; Meegahakumbura, Muditha K.; Kamunya, Samson; Muchugi, Alice; Möller, Michael; Liu, Jie; Xu, Jian-Chu; Ranjitkar, Sailesh; Li, De-Zhu; Gao, Lian-Ming (Frontiers in Plant Science, 2016)
Africa is one of the key centres of global tea production. Understanding the genetic diversity and relationships of cultivars of African tea is important for future targeted breeding efforts for new crop cultivars, specialty tea processing and to guide germplasm conservation efforts. Despite the economic importance of tea in Africa, no research work has been done so far on its genetic diversity at a continental scale. Twenty-three nSSRs and three plastid DNA regions were used to investigate the genetic diversity, relationships and breeding patterns of tea accessions collected from eight countries in Africa. A total of 280 African tea accessions generated 297 alleles with a mean of 12.91 alleles per locus and a genetic diversity (HS) estimate of 0.652. A STRUCTURE analysis suggested two main genetic groups of African tea accessions which corresponded well with the two tea types Camellia sinensis var. sinensis and C. sinensis var. assamica respectively, as well as an admixed “mosaic” group whose individuals were defined as hybrids of F2 and BC generation with high proportion of C. sinensis var. assamica being maternal parents. Accessions known to be C. sinensis var. assamica further separated into two groups representing the two major tea breeding centres corresponding to southern Africa (Tea Research Foundation of Central Africa, TRFCA) and East Africa (Tea Research Foundation of Kenya, TRFK). Tea accessions were shared among countries. African tea has relatively lower genetic diversity. C. sinensis var. assamica is the main tea type under cultivation and contributes more in tea breeding improvements in Africa. International germplasm exchange and movement among countries within Africa was confirmed. The clustering into two main breeding centres, TRFCA and TRFK, suggested that some traits of C. sinensis var. assamica and their associated genes possibly underwent selection during geographic differentiation or local breeding preferences. This study represents the first step towards effective utilization of differently inherited molecular markers for exploring the breeding status of African tea. The findings here will be important for planning the exploration, utilization, and conservation of tea germplasm for future breeding efforts in Africa.